AL-HALLAJ MENJEMPUT KEABADIAN - Abdul Munim Cholil (Bahasa Indonesia, 2024)
The study of Al-Hallaj has not been completed. No one dares to write about him except a century after his execution on March 26, 922 AD. The truth about his death is shrouded in mystery. The affair between politicians and ulama obscured the event. This study uses a historical criticism approach, by referring to classic books written a century after the tragedy -such as Ibn Bakuyah (426 H) which recorded directly from the son of Al-Hallaj (Hamad)-. The author also highlights the dialectical and socio-political relations that surround the story of Al-Hallaj without forgetting the psychology and existential consciousness of Sufis. So this study will be a new offer to be able to find a new paradigm regarding this most controversial figure.